2021
DOI: 10.1002/cncy.22436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic accuracy of bronchial brushing cytology in lung cancer: A meta‐analysis

Abstract: Background Flexible bronchoscopy is commonly used to examine patients suspected to have lung cancer. Bronchial brushing is one of the cytological technologies for lung specimens obtained through a bronchoscope. However, the accuracy of bronchial brushing cytology (BBC) for lung cancer diagnosis is still inconclusive. The aim of this study was to evaluate the diagnostic accuracy of BBC. Methods A literature search was conducted with PubMed, Embase, the Cochrane Library, Web of Science, Biomed Central, Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…A pooled analysis where no distinction was made between visible and non-visible lesions demonstrated a sensitivity of 67% and 37% for bronchial brushings and washings respectively. 28 However, a study assessing the diagnostic yield in non-visible parenchymal disease reported a yield of 37.3% and 46.4% for brushings and washings respectively, with a suggestion of improved yields when washings followed bronchial brushings. 29 Liquid-based cytology has gained favour over conventional smears and cytospin preparations, particularly for specimens containing abundant blood and/or mucus.…”
Section: Endob Ron Chial B Rus Hing S and Wa S Hing Smentioning
confidence: 99%
See 1 more Smart Citation
“…A pooled analysis where no distinction was made between visible and non-visible lesions demonstrated a sensitivity of 67% and 37% for bronchial brushings and washings respectively. 28 However, a study assessing the diagnostic yield in non-visible parenchymal disease reported a yield of 37.3% and 46.4% for brushings and washings respectively, with a suggestion of improved yields when washings followed bronchial brushings. 29 Liquid-based cytology has gained favour over conventional smears and cytospin preparations, particularly for specimens containing abundant blood and/or mucus.…”
Section: Endob Ron Chial B Rus Hing S and Wa S Hing Smentioning
confidence: 99%
“…The sensitivity of endobronchial brushings and washing for diagnosis of malignancy is influenced by whether the target lesion is visible or not. A pooled analysis where no distinction was made between visible and non‐visible lesions demonstrated a sensitivity of 67% and 37% for bronchial brushings and washings respectively 28 . However, a study assessing the diagnostic yield in non‐visible parenchymal disease reported a yield of 37.3% and 46.4% for brushings and washings respectively, with a suggestion of improved yields when washings followed bronchial brushings 29 …”
Section: Endobronchial Brushings and Washingsmentioning
confidence: 99%
“…Facilities to provide bronchial brushing and washings are few in LMICs, but FNAB either transthoracic or endobronchial ultrasound for lung malignancies seen on a chest X-ray shows sensitivity, specificity, and overall accuracy of 84%-96.29%, 95.45%-100%, and 89.55%-95.91%, respectively. [23][24][25][26][27][28] In a study that reported overall diagnostic characteristics (benign v malignant) of FNAB and CNB, the ranges of sensitivity were 81.3%-90.8% and 85.7%-97.4%; of specificity, 75.4%-100.0% and 88.6%-100.0%; and of accuracy, 79.7%-91.8% and 89.0%-96.9%, respectively. However, for specific diagnostic characteristics of FNAB and CNB (identifying the histologic subtype of malignancies or the specific benign diagnoses), the ranges of sensitivity were 56.3%-86.5% and 56.5%-88.7%; of specificity, 6.7%-57.1% and 52.4%-100.0%; and of accuracy, 40.4%-81.2% and 66.7%-93.2%, respectively.…”
Section: Cytopathology Is a Screening And Diagnostic Toolmentioning
confidence: 99%
“…The diagnostic yield of BB varies widely between studies, with a range of 18% to 87%. 20 Our study group previously mixed BALF and BB samples in a thin-layer prepared bottle to increase the diagnostic yield of BALF and BB. The results were published in a paper that demonstrated that the diagnostic value of LBC of BALF combined with BB was higher than that with BALF alone.…”
Section: Discussionmentioning
confidence: 99%